The role of assessment of quality of life and health with the index of vital activity in patients with arterial hypertension combined with gout in the family doctor practice. - O. M. Lazarenko; A. P. Kuzmina (Medičnì Perspektivi)
The number of studies that assess the quality of life of patients with various comorbid diseases is increasing annually. Arterial hypertension and gout is no exception. There are difficulties in managing this category of patients at the primary stage in accordance with current recommendations. The purpose of the study was to analyze the effectiveness of use of questionnaires for assessing the quality of life (SF-36) and health (HAQ) with disability index (DI) in patients with arterial hypertension combined with gout in everyday clinical practice by the family doctor; to assess the correctness of maintaining this category of patients in accordance with current recommendations (EULAR, 2016). A sociological survey of general practitioners (n=30) was carried out by a specially developed questionnaire consisting of three sections. It was found that not all doctors prescribe an adequate dose of colchicine for exacerbation of gouty arthritis, and more than half of the doctors do not use preventive colchicine for 3-6 months after the attack. Most doctors do not use the assessment quality of life (SF-36) and Health Assessment Questionare (HAQ) with a disability index (DI) at admission, but most believe that the results of these questionnaires contain important information on the patient's condition and the prospects for their using at the outpatient stage.